Evaluation of the range of motion of scapulothoracic, acromioclavicular and sternoclavicular joints: State of the art. (April 2023) - Giovannetti de Sanctis, Edoardo; Ciolli, Gianluca; Mocini, Fabrizio; Cerciello, Simone; Maccauro, Giulio; Franceschi, Francesco
The scapulothoracic, acromioclavicular and sternoclavicular joints play a fundamental role in the shoulder function. Shoulder complex kinematics have been studied with different methods using: goniometers, 2 static radiographs, 3D motion analyzers (invasive or noninvasive) and digital inclinometers. Goniometers have been used traditionally to assess scapular rotation in relation to the thorax. The intrinsic limit of multiple static two-dimensional shoulder radiographs is the attempt of describing in two what is occurring in three dimensions. Technology innovations have led to the development of the 3D shoulder complex kinematics analysis ETS (Electromagnetic tracking systems) using sensors (invasive bone-pin markers or noninvasive skin surface marker) stitched to the scapula/clavicula, thorax, and humerus. Despite being uncomfortable, invasive 3D motion cortical pins analyzers still represent the current gold standard for tracking shoulder complex kinematics. Therefore, access to three-dimensional biomechanical instrumentations for collecting kinematic data represents an active problem for many physicians. A precise, easy to use and low-cost non-invasive method able to draw and analyze the kinematics of the shoulder complex has not been developed yet. Further researches are necessary to design a new non-invasive method able to draw and analyze the kinematics of the scapula and the whole shoulder complex, precisely.